Identification of a cell population model for algae growth processes⁎This project has been supported by the Deutsche Forschungsge-meinschaft (DFG) with Grant number 395461267 and by Erasmus+ that has provided Federico Atzori with a scholarship for the internship at the Chair of Automatic Control at Kiel University. Issue 7 (2021) - Atzori, F.; Jerono, P.; Schaum, A.; Baratti, R.; Tronci, S.; Meurer, T.
Abstract: The growth process of a Chlamydomonas reinhardtii cell population is modelled with experimental data obtained in a batch reactor. To describe the growth process of this culture, the Droop model, extended by cell population balance model, is considered. On the basis of available measurements and the mathematical model, an optimization problem is defined in order to determine the kinetic parameter values for the growth functions of the Droop model and the cell division parameters of the cell population balance model.